2011
DOI: 10.1007/s10464-011-9444-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Housing Trajectories of Different Classes Within a Diverse Homeless Population

Abstract: The paper presents findings from a longitudinal study identifying different classes of homeless individuals in a mid-size Canadian city based on health-related characteristics and comparing the housing trajectories of these classes 2 years later. Using data collected through in-person interviews with a sample of 329 single persons who have experienced homelessness, the paper presents results of a latent class analysis. Results found four distinct latent classes characterized by different levels of severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 40 publications
(47 reference statements)
8
103
3
Order By: Relevance
“…The present study's identification of distinct subgroups of homeless frequent ED users parallels previous studies, which have identified heterogeneity among homeless individuals using latent class and cluster analyses (Aubry et al, 2012;Bonin et al, 2009;Kuhn & Culhane, 1998;Tsai, Kasprow, et al, 2013). Although differences in populations and measures used to examine heterogeneity make direct comparison difficult, our results are consistent with prior findings, which also identified relatively high-need subgroups of the homeless population with greater levels of services use.…”
Section: Discussionsupporting
confidence: 90%
“…The present study's identification of distinct subgroups of homeless frequent ED users parallels previous studies, which have identified heterogeneity among homeless individuals using latent class and cluster analyses (Aubry et al, 2012;Bonin et al, 2009;Kuhn & Culhane, 1998;Tsai, Kasprow, et al, 2013). Although differences in populations and measures used to examine heterogeneity make direct comparison difficult, our results are consistent with prior findings, which also identified relatively high-need subgroups of the homeless population with greater levels of services use.…”
Section: Discussionsupporting
confidence: 90%
“…[10][11][12] Additionally, the proportion of study participants who expressed a desire for paid employment in the community was lower at all sites than a previous US estimate. The American National Coalition for the Homeless, in a 2009 report on homelessness and employment, indicated that 86% of a sample of 182 homeless men and women had expressed a desire to work.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Income support can reduce the prevalence of risky and costly behaviours in this population. 6,7 Research suggests that homeless people with mental illness may have difficulty accessing disability benefits 8,9 and that their rate of unemployment exceeds 80%, [10][11][12] reducing their options for subsistence. Additionally, the highly visible act of panhandling is the focus of much public attention and has a negative impact on society's opinion of this vulnerable segment of society.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to having higher rates of drug use and drug use disorders, homeless populations may also experience added societal consequences due to their drug use. For example, among homeless individuals, those with drug use problems were shown to be less likely to achieve housing stability after two years, even when compared to homeless individuals with other physical and nondrug-related mental health disorders (12). To this end, beyond the adverse health risks of drug use, drug use is a strong barrier to establishing independent housing and is associated with the age at homelessness onset and duration of homelessness (12).…”
Section: Introductionmentioning
confidence: 99%